Uji Aktivitas Antioksidan Ekstrak Etanol Didemnum molle Yang Diperoleh Dari Pamtai Parentek Kabupaten Minahasa - Adithya Yudistira; Yuanita Amalia Hariyanto; Rizal Musafa Medica; Imam Jayanto (UNIVERSITAS SAM RATULANGI, 2024)
Didemnum molle is one of the tunicates marine biota whose habitat can be found in Indonesian coral reef waters. This marine animal is green which indicates the content of secondary metabolites as a form of self-defense. Secondary metabolite compounds in Didemnum molle have the potential to have antioxidant effects that can fight free radicals. This study aims to determine the antioxidant activity of Didemnum molle ethanol extract with DPPH method and calculation of percent inhibition value. The calculation results showed 47.94% (20 ppm), 58.75% (40 ppm), 60.45% (60 ppm), 63.15% (80 ppm), and 70.74% (100 ppm). These values indicate that all concentration series have antioxidant activity but are effective as antioxidants at concentrations of 40 ppm, 60 ppm, 80 ppm, and 100 ppm because they have a percent inhibition above 50%.